Drivers of the ECMWF SEAS5 seasonal forecast for the hot and dry European summer of 2022 - Patterson, M; Befort, DJ; O'Reilly, C; Weisheimer, A (Wiley, 2024)
The European summer (June–August) 2022 was characterised by warm and dry anomalies across much of the continent, likely influenced by a northward-shifted jet stream. These general features were well predicted by European Centre for Medium-Range Weather Forecasts' system 5 seasonal forecast, initialised on May 1. Such successful predictions for European summers are relatively uncommon, particularly for atmospheric circulation. In this study, a set of hindcast experiments is employed to investigate the role that initialisation of the ocean, atmosphere, and land surface played in the 2022 forecast. We find that the trend from external forcing was the strongest contributor to the forecast near-surface temperature anomalies, with atmospheric circulation and land-surface interactions playing a secondary role. On the other hand, atmospheric circulation made a strong contribution to precipitation anomalies. Modelled Euro-Atlantic circulation anomalies in 2022 were consistent with a La Niña-forced teleconnection from the tropical Pacific. However, a northward jet trend in the model hindcasts with increasing greenhouse gas concentrations also contributed to the predicted circulation anomalies in 2022. In contrast, the observed linear trend in the jet over the past four decades was a southward shift, though it is unclear whether this trend was driven by external forcings or natural variability. Nevertheless, this case study demonstrates that important features of at least some European summers are predictable at the seasonal time-scale.